SHAREHOLDER PARTICIPATION IN ANNUAL GENERAL MEETINGS UNDER NIGERIAN CORPORATE LAW: PHILOSOPHY, PRACTICE AND THE ROLE OF SHAREHOLDER ASSOCIATIONS (UUM Journal of Legal Studies, 2020)
Shareholders and board of directors in an annual general meeting (AGM) are the two organs of a company. Shareholders are legally empowered to participate in the AGM to meet directors and know about the performance of the company. Despite various philosophies (theories) and legal provisions on shareholder participation in AGMs, shareholders are still facing some challenges. Moreover, available literature in this area is limited in Nigeria. Therefore, this study seeks to examine various philosophies (theories), the law, cases and opinions of experts on shareholder participation, practices and the role of shareholder associations in protecting the rights of shareholders. The study adopted two methods of data collection. The first method was doctrinal legal research (library based) which mainly concerned statutory provisions under the Companies and Allied Matters Act 1990 (CAMA) and decisions of the court. The second method of data collection consisted of qualitative interviews with seventeen respondents regarding the theories, practices and role of shareholder associations in protecting the rights of shareholder participation in AGMs. The findings showed that shareholder participation can be supported by various theories including corporate personality theory; agency theory; contract theory; shareholder primacy; and corporate governance. The finding equally indicated that shareholders in Nigeria received notices of AGMs late, due to postal inefficiency and lack of recognition of ICT under the CAMA. Similarly, both regulators and shareholder associations have not done enough to protect shareholders and to improve their participation in AGMs. In view of this, there is a need for proactive measures to improve the participation of shareholders in AGMs. This is by amending the CAMA to incorporate provisions that will facilitate the effective service of notices of AGMs. Similarly, shareholder associations and regulators must take the responsibility of enlightening shareholders on their right of participation as well as how to enforce their rights in AGMs.